A new species of Nemoura Latreille (Plecoptera: Nemouridae) from Amur River Basin (South of the Russian Far East) - Teslenko, Valentina A.; Boumans, Louis (Zootaxa, 2018)
Nemoura sirotskii sp. n. (Plecoptera, Nemouridae) is described as a new stonefly species from the tributary streams of Zeya Reservoir (Amur River Basin) in the south of the Russian Far East. Detailed descriptions and illustrations are provided for the larvae and adult specimens. The diagnostic characters distinguishing it from sympatric species N. arctica are discussed.